Aerodynamic shape optimization of tiltrotor blades equipped with continuous morphing aerofoils - Pagano, A. (My University, 2015)
This document explores the adoption of morphing blades on tiltrotors with the aim of improving the rotor aerodynamic performance. Rotors for such aircrafts are designed to simultaneously address the peculiarities of both axial flights (hover, vertical ascent/descent and cruise) and edge flights (flyover). Some of the current aerofoil morphing technologies are investigated from the aerodynamic point of view so that the blade can modify its shape to meet the best rotor performance for the examined flight conditions. The potential benefits are discussed through the application of numerical procedures on a realistic tiltrotor geometry.
Keywords: Aircraft Design